2020
DOI: 10.15252/msb.20199416
|View full text |Cite
|
Sign up to set email alerts
|

Predicting antigen specificity of single T cells based on TCR CDR 3 regions

Abstract: It has recently become possible to simultaneously assay T‐cell specificity with respect to large sets of antigens and the T‐cell receptor sequence in high‐throughput single‐cell experiments. Leveraging this new type of data, we propose and benchmark a collection of deep learning architectures to model T‐cell specificity in single cells. In agreement with previous results, we found that models that treat antigens as categorical outcome variables outperform those that model the TCR and antigen sequence jointly. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…For example, ALICE is for detecting groups of homologous/expanded TCRs ( 13 ). TcellMatch uses cell-specific covariates (e.g., gene expression) but not TCR sequence alone as input, and its performance was tested on the noisy 10x Genomics Immune Map data without further cleanup ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ALICE is for detecting groups of homologous/expanded TCRs ( 13 ). TcellMatch uses cell-specific covariates (e.g., gene expression) but not TCR sequence alone as input, and its performance was tested on the noisy 10x Genomics Immune Map data without further cleanup ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…As next-generation screening technologies have increased the volume of available TCR-pMHC binding data, robust classifiers to computationally validate and subsequently predict TCR-pMHC–specific recognition are desired. While the results from initial TCR-pMHC binding classifiers are encouraging, most of them were only trained using CDR loop sequences or β-chain sequences alone and thus unable to learn the overall complex sequence patterns from full-length TCR sequences, resulting in suboptimal prediction accuracy for highly diverse pMHC binding TCRs ( 13 , 14 , 19 , 20 ). Leveraging the ability of deep learning algorithms to learn complex patterns, a couple of neural network–based classifiers were recently proposed ( 17 , 18 ) to uncover binding patterns in large, highly complex pMHC binding TCR sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Low counts of lymphocytes ( 11 ) and functionally impaired monocytes ( 8 ) make the patients susceptible to infection/reactivation of infective microorganisms. Effective T cell activation in response to a given pathogen needs the presence of a large number of lymphocytes to have a chance in finding cell having CDR3 able to align with the presented epitope ( 82 ). If it happens T cells may activate B cells having compatible membrane bound immunoglobulins named B cell receptor.…”
Section: Lymphocytes and Monocytes In The Pro-inflammatory Environmentmentioning
confidence: 99%
“…Another complicating factor is that despite the advent of single cell TCR paired chain sequencing, the currently available TCR-epitope binding data still mostly consists of single-chain (usually beta-chain) data, while in reality both the alpha and beta chains are thought to contribute to binding specificity. Indeed, recent studies have suggested that utilizing both chains could increase the accuracy of predictive TCR-epitope models [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%